Pastoral Konseling dalam Upaya Gereja Mengelolah Konflik Jemaat - Mourina G. Suwuh (PT. Giat Konseling Nusantara, 2025)
This research aims to make discoveries about the problems in congregational conflict and how to handle them. This research uses qualitative research methods with descriptive analysis to see and elaborate how the role of pastoral counseling has an impact in managing congregational conflict. The outcome of this research is that the role of pastoral care and pastoral counseling is a church service that can be an effective weapon. Therefore, it is very necessary to have a great awareness of all elements of church services, especially pastors, elders and deacons about the importance of pastoral assistance and pastoral counseling running well so that potential conflicts that may arise can be resolved together.